Consumption Value Dimension of Green Purchase Intention with Green Trust as Mediating Variable - Sari Dewi, Cynthia; Annas, Mohammad (Dinasti Publisher, 2022)
One of the sectors that pollute the environment is the cosmetics sector. Pay close attention to the packaging and microplastic waste that have been produced. Presently, the cosmetics company Garnier create a Garnier Green Beauty campaign to transform the company and lessen its impact on the environment. Garnier is working to produce cosmetics with more environmentally friendly formulae. By decreasing waste, it will be possible to reduce plastic pollution. This study examines what influences someone to use eco-friendly beauty products and be willing to purchase Garnier products. Quantitative research techniques were used in this investigation. 211 respondents fit the criteria for knowing about Garnier products but had never used them. The results of the study show that the intentions of consumers to make green purchases are significantly influenced by the functional value, social value, and emotional worth of various goods. However, social work has little impact on green trust.